The nature of a lady [large type] - White, Roseanna M. (The secrets of The Isles, 2021)
"Fleeing to the beautiful Isles of Scilly, Lady Elizabeth Sinclair stumbles upon dangerous secrets left behind by her cottage's former occupant, and agrees to help the missing girl's brother, Oliver Tremayne, find his sister. As the two work together, they uncover ancient legends, pirate wrecks, betrayal, and the most mysterious phenomenon of all: love"--